Model Pertumbuhan Ekonomi Indonesia: Peranan Ketergantungan Spasial - Aspiansyah, Aspiansyah; Damayanti, Arie (UI Scholars Hub, 2019)
This study aims to examine the role of spatial dependence on Indonesia’s regional economic growth based on panel data of all provinces in Indonesia during 1990–2015. By using spatial Durbin model, the authors found that spatial dependence plays an important role in achieving regional economic growth in Indonesia. Indonesia’s regional economic growth model that controls spatial dependence, yields better estimates than growth model that does not control spatial dependence. The researchers also found positive spatial spillover to Indonesia’s regional economic growth sourced from other region’s economic growth and initial per capita incomes, as well as population growth in other regions.